Pengaruh Konten Marketing Terhadap Keputusan Pembelian Produk Fashion Muslim Di Tiktok Pada Masyarakat Desa Kopo - Siva Agustina; Harry Nugraha (Jurnal Mirai Management, 2025)
This study aims to analyze the effect of content marketing on purchasing decisions for Muslim fashion products on TikTok in Kopo Village community. The growth of internet users and digital marketing, especially through platforms such as TikTok, has driven changes in consumer behavior in the rapidly growing Muslim fashion industry in Indonesia. However, there is still a research gap regarding the specific impact of content marketing on TikTok on Muslim fashion purchasing decisions in rural areas. This study used a quantitative approach. Data were collected through online questionnaires from 89 respondents in Kopo Village aged 20-34 years old, selected using purposive sampling technique. Data analysis includes descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression analysis, coefficient of determination, and T test. The results of descriptive analysis show that respondents rated the marketing content of Muslim fashion on TikTok as easy to understand and easy to find. The T test results show that marketing content has a positive and significant effect on purchasing decisions for Muslim fashion products, with a calculated t value greater than the t table. The coefficient of determination of 0.458 indicates that 45.8% of the variation in purchasing decisions is explained by marketing content, while 54.2% is influenced by other factors outside the research model. The conclusion of this study is that marketing content has a positive and significant influence on purchasing decisions for Muslim fashion products on TikTok in Kopo Village community. Keywords : Content, Purchase Decision, Fashion, Tiktok